Investigating Asian regional income convergence using Fourier Unit Root test with Break - Yaya, OlaOluwa S.; Furuoka, Fumitaka; Pui, Kiew Ling; Jacob, Ray Ikechukwu; Ezeoke, Chinyere Mary (Elsevier, 2020)
Income convergence among countries has become an important topic in international economics. This paper uses a new unit root test, namely the Fourier Unit Root test with Break, to examine income convergence in nine Asian countries. It has grouped the countries into three regions in Northeast Asia, Southeast Asia, and South Asia and has chosen three major economies in each of the three areas for empirical analysis. The empirical findings indicate that there is relatively greater income convergence in the South Asia and that there is a mixed trend of income convergence and income divergence in Northeast Asia and Southeast Asia. © 2019 CEPII (Centre d'Etudes Prospectives et d'Informations Internationales), a center for research and expertise on the world economy